Analisis morfo-fonologi perkataan pinjaman Bahasa Inggeris dalam Bahasa Arab / Syahirah Almuddin - Syahirah, Almuddin (2012)
The research of “ Morpho-phonological analysis of English Loanwords in Arabic” discuss about the change of phonology and morphology aspects that happen in English loanwords in Arabic. In foreign loanwords the questions that arise are either the word is borrowed entirely by way of spelling similarization or to be taken part of it and been similarize with pattern that in the targeted language at the same time the phonology similarization. Thus this research is to fulfill three main objectives that are to identify English loanwords in Arabic, analyse the process that happen in phonology similarization and morphology of these words and how the main morpho-phonology change in those words. The data has been collected from Arabic dictionary “al-Mu‘jam al-Wasit “. 70 words has been choosed and analyzed by way of transcription and analyzing the changes that happen from original language which is English into Arabic from the aspect of the change of sound and the change of morphology. The result is, most of the changes that happen to the sound there is not exist in Arabic. These sounds have been suits by taking the closes sounds from the articulation mode and articulation place. There are also sound changes from the original sound in Arabic cause by the environments. This research also shows there is no specify law method that can be done from morpho-phonology analyzation English loanwords into Arabic.